Penerapan Studi Neuromarketing pada Desain Kemasan Produk Hijau dan Pengukuran Niat Beli Berdasarkan Profil Gender, Pendidikan, dan Frekuensi Membeli Produk - Listia Chaerani, Metha; Hasrini Sari (Journal of Research in Industrial Engineering and Management, 2023)
The significant growth in the beauty and skincare sector, especially in natural skincare products, is driven by the high trend of adopting a healthy lifestyle and using environmentally friendly products. One of the strategies used is marketing through product packaging. This is because product packaging serves as an effective communication medium between consumers and the product. In this study, the design of packaging elements for natural skincare products, such as eco-labels, was tested using eye-tracking technology. Heatmaps showed that yellow to red areas appeared on almost the entire general information labels of the stimuli. The ANOVA results indicated no differences in visual attention based on gender and level, while differences in the frequency of purchasing green products showed differences in visual attention to natural skincare products. Additionally, the intention to purchase green products was also measured based on gender, education, and the frequency of buying green products. The ANOVA results revealed that only the variables of education level and frequency of buying products showed differences in the intention to purchase natural skincare products.